Highly stable 1T-MoS2 by magneto-hydrothermal synthesis with Ru modification for efficient hydrogen evolution reaction. Issue 39 (16th September 2022) - Zhu, Lili; Wang, Zheng; Li, Changdian; Li, Han; Huang, Yanan; Li, Hui; Wu, Ziqiang; Lin, Shuai; Li, Neng; Zhu, Xuebin; Sun, Yuping
Abstract : Ru/1T-MoS2 with excellent hydrogen evolution activity were designed by a two-step method of phase engineering and noble metal modification. The reasons behind its excellent hydrogen evolution activity were revealed experimentally and theoretically. Abstract : Obtaining highly stable 1T-MoS2 is very crucial to investigate the hydrogen evolution reaction (HER) due to the thermodynamically metastable characterization of 1T-MoS2 . Currently, the preparation of pure phase and stable 1T-MoS2 is a big challenge, which limits the investigation of MoS2 as an electrocatalyst for better HER performance. In this study, highly stable MoS2 with different 1T content was prepared by magneto-hydrothermal synthesis, showing that the pure 1T-MoS2 has the best HER performance with an overpotential of 189 mV at the current density of 10 mA cm −2 amongst the MoS2 electrocatalysts with different 1T content. Furthermore, magneto-hydrothermal-synthesized highly stable and pure 1T-MoS2 was modified with Ru nanoparticles to improve the HER activity, delivering very low overpotential of 81 mV at a current density of 10 mA cm −2, small Tafel slope of 54 mV dec −1 as well as long stability. Theoretical analysis based on density functional theory shows that 1T-MoS2 has a lower Gibbs free energy change of adsorbed hydrogen (Δ G H* ) (1.26 eV) as compared with that of 2H-MoS2 (1.96 eV), and 1T-MoS2 with Ru modification will obviously suppress the Δ G H* (0.02 eV). This work confirms that 1T-MoS2 is efficient as an HER catalyst and Ru modification can further improve the electrocatalytic HER activity.